Generic Sharia Governance and Expertise in Indonesian Digital Islamic Bank Ecosystem - Moeljadi Moeljadi; Triningsih Sri Supriati; Hary Soegiri (International Journal of Emerging Issues in Islamic Studies, 2022)
The implementation of Islamic Bank is still way too far from maturity due to the fact that questionably asymmetrical practices and letterlijk practices of Syaria Compliance. It’s no wonder that consumers have troublesome experience in distinguishing between the Islamic Banks and the conventional counterparts, leading them to believe that the Islamic Banks have the same process with the conventional ones come with only labels to differentiate. Indonesia comes with the advantage of moderation, but in the other hand, it offers the dynamic demand of Islamic Bank adoption than makes the infant Islamic Bank practices become even more challenging in this digitalization. On this subject, the capacuty of Islamic banks to maintain current customers loyalty while attracting new ones by demonstrating the generic value of Islamic Bank as implemented in good corporate governance and sharia expertise human capital is a significant determinant of the Islamic banks performance and sustainability in the digital industry. This meta-analysis, based on recent studies, provides a broader perspective of Islamic Bank, stating that Islamic Bank is more than just a unique system based on specific compliance to specific rules (Sharia Law), but the implementation of Good Corporate Governance and Sharia Expertise Human Capital, both of which serve as the generic product of Islamic Bank. This study allows banking supervisors, boards of chiefs, and other stakeholders to be more proactive in the current ongoing sharia governance discourse and raise concerns about the current implementations.